The process of gathering evidence in civil cases: its application in civil and shariah courts - Mohamed, Duryana; Abas, Afridah (LexisNexis, 2011)

(untitled)
The process of gathering evidence is also known as a pre-trial process. Its objective is to gather relevant evidence before the trial. This process is very important since both parties must produce only relevant, relia-ble and authentic evidence in order to establish a reasonable claim or defence. Nevertheless, in the civil court, the procedures of gathering evidence seems to be more detailed and applicable to all types of civil cases whereas the Shariah Court the procedures for gathering evidence is quite limited and confined to li-mited cases only. This is evidence in the relevant procedural rules laid down in both civil court procedure and the Shariah Court civil procedure. This paper discusses the above process by referring to the Rules of the High Court 1980 and the Shariah Court Civil Procedure (Federal Territory) with the objective of providing re-levant information on the process of gathering evidence in civil cases for both courts. The discussion will also examine the possibility of harmonising any relevant procedures in the civil procedure rules. It is also hoped that the discussion will provide useful guidelines in enhancing the above process.